2019
DOI: 10.3390/jmse7050136
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Hydrodynamic Noise of 3D Hydrofoil with Spanwise Microgrooved Surfaces Inspired by Sharkskin

Abstract: Loud hydrodynamic noise is not only potentially harmful to the health of organisms in the ocean, but it is also a threat to the survival of underwater vehicles. Different from the general noise reduction technologies at present, a new idea for a flow-induced noise reduction design with spanwise microgrooved surfaces inspired by sharkskin is introduced in this paper. Large eddy simulations (LES) combined with the Ffowcs Williams and Hawkings (FW-H) equation are adopted to simulate the hydrodynamic noise of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Like wind turbines, the vertical axis turbines are much quieter compared with the horizontal types, and the horizontal axis turbines often generate low-frequency noise at blade passing frequency and higher order harmonics, which are harmful to the environment [17]. This phenomenon has also been confirmed by the research group from Northwestern Polytechnical University, with a series of continuous research [4,5,7,8,18]. In fact, the HAHT investigated in this paper and the horizontal axis wind turbines are similar to the rotating machinery of renewable energy.…”
Section: Introductionmentioning
confidence: 90%
“…Like wind turbines, the vertical axis turbines are much quieter compared with the horizontal types, and the horizontal axis turbines often generate low-frequency noise at blade passing frequency and higher order harmonics, which are harmful to the environment [17]. This phenomenon has also been confirmed by the research group from Northwestern Polytechnical University, with a series of continuous research [4,5,7,8,18]. In fact, the HAHT investigated in this paper and the horizontal axis wind turbines are similar to the rotating machinery of renewable energy.…”
Section: Introductionmentioning
confidence: 90%
“…Moreover, they found that at higher inflow speeds, this design is more effective in suppressing lift fluctuations and reducing noise. Dang et al [192] achieved further advancements in noise reduction technologies for underwater vehicles by developing a transverse micro-groove surface, inspired by the texture of shark skin. This innovative surface, as depicted in Figure 20, was specifically designed to reduce the hydrodynamic noise of hydrofoils.…”
Section: Applications Of Biomimetic Noise Reductionmentioning
confidence: 99%
“…This explanation has been later corroborated. 84 The suppression of lateral fluctuations and the capture of small-scale vortices are used to explain the drag reduction of the riblets; 85 also, the complexity of the shark scales is considered to be due to the simplified riblet only, which implied drag reduction mechanism; thus, real and highly similar shark skins, whose surface is covered by denticles, have also been hydrodynamically tested to explain the reason for shark skin drag reduction.…”
Section: Biological Prototypesmentioning
confidence: 99%
“…The structure of spanwise riblet inspired by sharkskin has been applied to simulate the hydrodynamic noise of the three-dimensional (3D) hydrofoil and the maximum noise reduction was observed at 7.28 dB. 84 The blade bionic groove design proposed by J. Wang, Nakata, and Liu 203 was applied to the mixed flow fan and it was found that the use of the groove structure has the potential to suppress noise. When the aerodynamic efficiency loss is only 0.3 percentage points, the blade leading edge reduces the turbulent flow energy by about 38%.…”
Section: Applicationsmentioning
confidence: 99%